Effect of defect geometries upon burst capacity of composite repaired pipe - Tay, Hong Wei (2019)
Nowadays, composite wrap repair has been proven effective in repairing pipeline system. This method provides several advantages such as lightweight, excellent fatigue and corrosion resistance. Despite many advantages offered by composite repair system, several issues regarding the factors that influencing the behaviour and performance of this system are not fully understood. Effect of defect geometries of composite repaired pipe is one of the factors that may affect the burst capacity of a composite repaired pipe. However, existing design code only considered defect depth in calculating the burst pressure of the composite repaired pipe. Recently, there are some researches proved that the geometries (length and width) will affect the burst pressure of bare pipe, hence there is high possibility that the defect geometries will also affect the burst pressure of composite repaired pipe. Thus, the objective of this study is to explore the potential effect of defect geometries of composite repaired pipe towards its burst capacity through finite element analysis. Four composite repaired pipe models were developed to study the influence of defect geometries (length and width) towards the hydrostatic burst pressure of composite repaired pipeline. The result proved that as the dimension of defect geometries increased, the burst pressure of the composite repaired pipe has decreased. The difference in burst pressure was found to be about 20% between the largest and the smallest defect dimension of composite repaired pipe model used in this study. As a conclusion, the defect geometries (length and width) does affect the burst capacity of composite repaired pipe and the findings can be used for future research in optimizing the design of pipeline rehabilitation system especially solve the problem of conservativeness in existing design codes.